TINGKAT KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR DESA BINA BARU KECAMATAN KULO KABUPATEN SIDENRENG RAPPANG - Masnah; Adnan, Andi Astina; Sellang, Kamaruddin (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to determine the level of human resource competency on the quality of public services at the Bina Baru Village Office, Kulo District, Sidenreng Rappang Regency and to determine the quality of public services at the Bina Baru Village Office, Kulo District, Sidenreng Rappang Regency. The population and sample in this research were 52 people who received services in May and June 2023 at the Bina Baru Village Office. The sampling technique used was a saturated sample. This type of research is quantitative descriptive. The data collection techniques used were observation, interviews, literature study and questionnaires. The data analysis technique used is descriptive statistics and with the help of the SPSS version 21 application. The research results show that the Human Resources Competency Level at the Bina Baru Village Office is in the "poor" category with a percentage of 58%. The quality of public services at the Bina Baru Village Office is in the "poor" category with a percentage of 60%. The Competency Level of Human Resources on the Quality of Public Services at the Bina Baru Village Office, Kulo District, Sidenreng Rappang Regency is in the "Significant/Influential" category. significant, and the probability is far above 0.005, based on the calculated t value > t table or 3,483 ≥ 1,676, then H0 is rejected, meaning that the Competency Level of Human Resources is Significant/Influences the Quality of Public Services at the Bina Baru Village Office, Kulo District, Sidenreng Rappang Regency.